Penerapan Teknik Group Investigation Untuk Meningkatkan Keterampilan Menulis Teks Deskripsi Siswa Didik Kelas VII SMP Bhinneka Tunggal Ika Pasuruan - Gatut Setiadi (Universitas Yudharta Pasuruan)
Writing skills are the main thing in learning Indonesian, because these skills become a basic aspect of a child's language ability. A child's writing skills require a continuous process at every level of education. So this study aims to improve the writing skills of text description for VII grade students of Bhinneka Tunggal Ika Pasuruan Middle School by using group investigation techniques. The approach used in this study is a qualitative approach to the type of class cycle research design (CAR). In order to achieve maximum results, this study was conducted in three cycles, namely pre cycle, cycle I, and cycle II. In the pre cycle, collecting data from the results of the implementation of the learning of writing description text skills without using group investigation techniques. In cycle I and cycle II the researchers carried out learning using group investigation techniques. Each cycle includes 1) planning, 2) implementation, 3) observation, and 4) reflection. The research subjects were 36 M grade students of Bhinneka Tunggal Ika Pasuruan Junior High School as many as 36 students. In the cycle before the process of writing description text skills reached 53% and 71% in the first cycle, while in the second cycle the results of writing description text skills reached 81%. Increased students' writing skills due to using group investigation (GI) techniques they collaborate in working on writing descriptive text